Swimming to Europa. - Kumagni, J. (IEEE spectrum)
The paper discussed about a field test of one of the most intelligent and agile underwater robots ever crafted, a possible predecessor of a machine that might someday swim the vast, ice crusted ocean of Jupiter's mysterious moon Europa. Called DEPTHX, for deep phreatic thermal explorer, the 1.3-metric-ton machine can maneuver freely, draw detailed, three-dimensional maps of its environment. Most important, it does all that without any guidance from human operators.